Kajian Semantik Kognitif Verba Konsonan Tadayou - Ardana, Nabila Meisya; Hariri, Tatang (East Asian Review, 2024)
The Japanese language has many words that have more than one meaning. One of these words is the consonant verb ‘tadayou’. This study used a qualitative research method that aimed to identify the classification of the meaning of the consonantal verb tadayou and its interlanguage relationship. The data were taken from the NINJAL-LWP for TWC corpus and then analyzed using cognitive semantic theory. This research found that the basic meaning of tadayou consonant verbs is hovering. Then, tadayou consonantal verbs have eight expanded meanings, namely 1) float, 2) wander, 3) emit (scent, etc.), 4) (setting) atmosphere, 5) agitated, 6) unstable, 7) flinch, and 8) feel (feeling). However, the meanings of “agitated”, “unstable”, and “flinch” found no place of relevance nowadays. Outside of these classifications, one new meaning was found in this study, namely “to permeate”. In addition, there was an exception that abstract objects can be used for the meaning of “levitate”. The structural metaphorical expansion of the meaning of the consonantal verb tadayou was “wandering”. The ontological metaphorical expansion of meanings was “emit (scent, etc.)” and “atmosphere” (setting). Lastly, the metonymical expansion of meaning was “to float”, “to feel (feeling)”, and “to permeate”.